Lessons on environmental health and disaster preparedness, response and recovery from the severe Kelantan flooding in 2014. (18th April 2019) - Radi, Mohd Firdaus Mohd; Hashim, Jamal Hisham; Jaafar, Mohd Hasni; Hod, Rozita; Ahmad, Norfazilah; Nawi, Azmawati Mohammed; Baloch, Gul Muhammad; Ismail, Rohaida; Ayub, Nur Izzah Farakhin
Flood is a natural disaster that occurs annually in Malaysia causing devastating effects and damages to property and lives. This study looks into our environmental health and disaster preparedness, response and recovery management throughout the severe 2014 Kelantan flooding. We conducted three focus group discussions (FGDs) with healthcare, rescue and welfare workers, and community representatives involved throughout the disaster. The unprecedented severe flooding affected our environmental health and disaster management leading to various prominent issues. State level officers faced greater challenges in inter-agency communication, coordination and collaboration. District level staff faced more complications during disaster and emergency response. Meanwhile, community representatives faced issues pertaining to their livelihood mainly during and after the disaster. Recommendations include improved coordination, effective communication, improved human resource management, accessible early warning system, community empowerment and awareness, and prioritisation of continuous environmental health services. We hope that these recommendations can improve our future disaster management.